The political geography of economic nationalism - Koch, Natalie (Handbook of Economic Nationalism, 2022)
This chapter surveys the key political geography concepts that underpin the diverse expressions of economic nationalism across the world and through different historical moments. Recognising that economic nationalism cannot be conceptualised as doctrine comprised of essential elements, the chapter theorises economic nationalism as a political discourse that operates through mobilising various narratives or storylines about political space, grouped around the three conceptual nodes of the nation, sovereignty, and geopolitics. Since economic nationalism cannot be explained outside of specific historical contexts, the chapter illustrates how these conceptual nodes have been mobilised by actors in many contexts, often with starkly divergent political and material implications. Specific examples are drawn from around the world to showcase the sheer diversity of expressions of economic nationalism, which the tools of political geography can help to elucidate.
Gesehen am 05.12.2022